Discourse Analysis in Developing Multimodal E-Book Teaching Materials using Book Creators in Psycholinguistics Lessons - Barus, Frinawaty Lestarina; Harahap, Safinatul Hasanah; Naelofaria, Salmah; Simanjuntak, Emasta Evayanti (ppjbsip, 2024)
This study aims to conduct discourse analysis for the development of multimodal ebook teaching materials using book creators in psycholinguistics lessons at Universitas Negeri Medan. Engaging with over a hundred students from the Indonesian Language and Literature Education Study Program, the research embarks on an exploratory journey. Through meticulous discourse analysis, the inquiry seeks to comprehend student engagement and preferences within the domain of psycholinguistics. Employing a thorough methodology involving observations, interviews, and questionnaires, the study unveils prevalent pedagogical trends and identifies avenues for progress. While conventional textbooks and journals remain prominent, students demonstrate a distinct inclination towards digital resources, signaling a burgeoning demand for immersive learning experiences. Introducing multimodal ebooks, poised to revolutionize education with dynamic and interactive content, the research endeavors to leverage state-of-the-art book creation technology. By tailoring teaching materials to the nuances of psycholinguistic pedagogy, the study aims to foster enthusiasm among learners and empower them with engaging educational tools.